Temple Destruction, Mourning and Curse in Elephantine, with a View to Lamentations - Granerød, Gard 1975- (2020)
The article discusses the lament over the Temple of YHW in Elephantine from three angles: from the perspective of the internal rhetoric or composition of the letter, from the perspective of the world of the Judaeans who wrote the petition, and from the perspective of the world of the intended recipient of the letter. In addition, the article explores how the mention of collective mourning and curse in the petition letter from Elephantine may provide a text of comparison - and context - for the laments over the destruction of the city of Zion and her temple found in the Book of Lamentations.
L’article discute les complaintes sur le Temple de YHW à Eléphantine sous trois angles: de la perspective de la rhétorique interne ou de la composition de la lettre, de la perspective du monde des Judéens qui ont écrit la pétition, et de la perspective du monde des récipiendaires de la lettre. De plus, l’article explore en quoi la mention d’un deuil collectif et d’une malédiction dans la lettre de pétition d’Eléphantine peut fournir un texte de comparaison - et un contexte - pour les lamentations sur la ville de Sion et de son temple, telles qu’on les trouve dans le livre des Lamentations.
Der Artikel diskutiert die Klage über den Tempel des JHWH in Elephantine aus drei Blickwinkeln: aus der Perspektive der inneren Rhetorik oder Komposition des Briefes, aus der Perspektive der Judäer, die die Petition verfasst haben, und aus der Perspektive des vorgesehenen Empfängers des Schreibens. Darüber hinaus wird untersucht, inwiefern die Erwähnung von kollektiver Trauer und Fluch im Petitionsschreiben von Elephantine einen Vergleichstext und Kontext zu den Klagen über die Zerstörung der Stadt Zion und ihres Tempels im Buch Threni bietet.